Finite Element Analysis for Design Engineers - Kurowski, Paul M. (Warrendale SAE International, 2023)
Finite Element Analysis (FEA) has been widely implemented by the automotive industry as a productivity tool for design engineers to reduce both development time and cost. This essential work serves as a guide for FEA as a design tool and addresses the specific needs of design engineers to improve productivity. It provides a clear presentation that will help practitioners to avoid mistakes. Easy to use examples of FEA fundamentals are clearly presented that can be simply applied during the product development process.
Includes bibliographical references and index
Keywords: Công nghệ kỹ thuật ô tô